Activision: demystifying the undervalued player - the gaming bargain of the year - Costa, Diogo Alexandre Lima da (2022)
The purpose of this thesis is to examine Activision Blizzard with the objective of making a Buy/Sell/Hold recommendation. Despite the recent turmoil surrounding the stock, following the revelation of sexual harassment within the firm, we believe the company is poised for an exciting future. Besides the strong fundamentals, the company is well positioned toga in from market trends, such as the rise of e-sports, rising demographics and increasing internet penetration rates in developing countries. This analysis concludes with a Buy recommendation for the stock, which, due to recent turbulence, we believe is significantly undervalued. As of December 31st,of 2022, we expect Activision Blizzard’s stock price to be $76.40, resulting in a 31% total shareholder return.